40-YEAR BIBLIOMETRIC ANALYSIS OF WAQF: ITS CURRENT STATUS AND DEVELOPMENT, AND PATHS FOR FUTURE RESEARCH - Khaled Nour Aldeen (Journal of Islamic Monetary Economics and Finance, 2021)
Waqf (Islamic endowment) has received great attention from contemporary scholars, in line with the increasing attention being paid to social welfare. However, it is conceptually unclear, with no consensus having been reached among researchers on its current status. This study provides a brief overview of recent Waqf research developments, hence paving the way for future research. The research employs a bibliometric approach to analysing and summarising the trends and status quo in Waqf growth. Only articles written in English extracted from both the Web of Science and Scopus databases were considered for the study. The paper is an attempt to establish a solid conceptual base and to suggest directions for future research. The research provides a clear picture of the growth of Waqf, and indicates research gaps by reaching comprehensive conclusions about what has been achieved in the field. It hence opens new doors for scholars to develop innovative Waqf models to bridge socioeconomic issues. Our findings show that Indonesian and Malaysian scholars and their educational institutions have had a robust research commitment to the theme of Waqf during the last forty years. However, there is a lack of research on the countries where Waqf was first practised.